Multibranch convolutional neural network with contrastive representation learning for decoding same limb motor imagery tasks - Phunruangsakao, Chatrin; Achanccaray, David; Izumi, Shin-Ichi; Hayashibe, Mitsuhiro (Frontiers in Human Neuroscience, 2022)
Emerging deep learning approaches to decode motor imagery (MI) tasks have significantly boosted the performance of brain-computer interfaces. Although recent studies have produced satisfactory results in decoding MI tasks of different body parts, the classification of such tasks within the same limb remains challenging due to the activation of overlapping brain regions. A single deep learning model may be insufficient to effectively learn discriminative features among tasks. Therefore, the present study proposes a framework to enhance the decoding of multiple hand-MI tasks from the same limb using a multi-branch convolutional neural network. The CNN framework utilizes feature extractors from established deep learning models, as well as contrastive representation learning, to derive meaningful feature representations for classification. The experimental results suggest that the proposed method outperforms several state-of-the-art methods by obtaining a classification accuracy of 62.98% with six MI classes and 76.15% with four MI classes on the Tohoku University MI-BCI and BCI Competition IV datasets IIa, respectively. Despite requiring heavy data augmentation and multiple optimization steps, resulting in a relatively long training time, this scheme is still suitable for online use. However, the trade-off between the number of base learners, training time, prediction time, and system performance should be carefully considered.